Genetic passport as a basis for primary and secondary prevention of cerebral infarction in young people - T. I. Dutova; I. N. Banin; N. A. Ermolenko (Лечащий Врач)
Background. Numerous studies on the investigation of genetic risk factors for ischemic stroke development prove the multifactorial nature of the pathology, when several genes are simultaneously involved in its development, which have a determinative effect on various links of its pathogenesis. Revelation of the genetic predispositions for stroke development is an important factor in its primary and secondary prevention, especially in young and middle-aged people hereditary tainted.Objective. To develop comprehensive clinical and genetic criteria for various pathogenetic variants of ischemic stroke (IS) to control the preventive measures for primary and secondary disorders of cerebral circulation.Materials and methods. The genetic, clinical and laboratory results of the examination of 280 patients with ischemic stroke (IS) have been analyzed. Group I consisted of young age patients, n = 180, aged 22 to 45 years (mean age 33.4 ± 6.57), including 55% of women and 45% of men. 38 young age patients of group I (21,11%) experienced recurrent ischemic stroke. Group II included elderly patients with ischemic stroke (n = 50), aged 52 to 100 years (mean age 73.4 ± 8.24 years), including 70% of women and 30% of men. Group III, the control one, consisted of apparently healthy young age individuals (n = 50), aged 20 to 43 years (mean age 31.5 ± 5.82 years), including 45% of women and 55% of men. Venous blood tests were once performed in all the subjects to reveal genetic polymorphisms of the hemostasis system, the immune response, the endothelial function, and the lipid metabolism. Results. Significant factors of the probability of ischemic stroke development due to polymorphism of genes controlling hyperhomocysteinemia have been revealed: methylenetetrahydrofolate reductase MTHFR (A1298C) (р = 0,012),methionine synthase MTR (A2756G) (р = 0,014), methylenetetrahydrofolate reductase MTHFR (C677T) (р = 0,024); arterial hypertension: angiotensin receptor IIAGTR1 (A1166C) (р = 0,097), G-protein beta 3 GNB3 (C 825T) (р = 0,108); immune response: interleukin-6 (G-174 C) (р = 0,007); aspirin resistance: platelet receptor fibrinogen GP III a (HPA1-1 a/1 b) р = 0,0883; plasminogen activator inhibitor PAI-1 (5G/4G) (р = 0,106). A higher coefficient of ischemic stroke development (1.79 = 0.07), depending on genetic polymorphism, has been revealed in young people than in elderly patients and healthy donors. It has been established that the presence of mutations in the genes controlling hyperhomocysteinemia, the immune response, and the blood clotting system is of important pathogenetic importance in predicting the risk of ischemic stroke at a young age. The data obtained indicate the expediency of including genetic research in the standard of ischemic stroke diagnosis in young people, which will allow us to optimize diagnostic methods and develop the measures to prevent recurrent cases of the pathology.Conclusion. The study of the contribution of risk factors to the probability of ischemic stroke development has led us to the development of the methodology for primary and secondary prevention of cerebral infarction, which currently is a topical task, the solution of which lies both in the fields of medical genetics and clinical neurology